Influence of precipitations and sunshine hours on yield of paddy field grown wheat (Triticum aestivum L.) in Northern Kyushu, Japan. (2nd October 2019) - Nishio, Zenta; Uchikawa, Osamu; Hideshima, Yoshitomo; Nishioka, Hiroyasu; Mihara, Minoru; Nakamura, Kazuhiro; Matsunaka, Hitoshi; Yamaguchi, Kikuichiro
ABSTRACT: Relationships between wheat ( Triticum æstivum L.) yield components and growing season weather conditions ( e.g . temperature, precipitation, and sunshine duration) were investigated for a rice-wheat rotation paddy system situated in Northern Kyushu, Japan over a 17-year period (2000–2016). A 1.0 mm increase in precipitation from 21 to 32 days after sowing decreased wheat yield by about 27 kg ha −1 at early seedling stage with one to two leaves (Zadoks (Z) growth stage Z1.1–1.2). Number of tillers and spikes showed significant negative correlations to the amount of precipitation during the period. An hour increase in mean daily sunshine hours from 94 to 111 days after sowing resulted in an 328 kg ha −1 rise in grain yield at stem elongation stage with the first and second node detection (Z3.1–3.2). The grain number per square meter also showed strong positive correlations to sunshine hours during the same period. However, this positive effect of sunshine was negated when precipitation exceeded about 30 mm during the early seedling stage. Consequently, precipitations at early seedling stage and sunshine hours at stem elongation stage mostly determined wheat yield in Northern Kyushu paddy field. Increasing precipitations during the early seedling stage highlights the pressing need for effective paddy field drainage management from wheat sowing through harvest. Abbreviations : CP: Chikushi Plains; FARC: Fukuoka prefectural Agriculture and Forestry Research Center; SARC: Saga prefectural Agricultural Research Center; DAS: days after sowing Graphical Abstract: Graphical Abstract: